Endosulfan promotes cell growth, migration and invasion via CCL5/CCR5 axis in MCF-7 cells - Zeming Liu; Xiaolin Ding; Boxiang Zhang; Yue Pang; Yuhui Wang; Dan Xu; Hailong Wang (Ecotoxicology and Environmental Safety)
Endosulfan, recognized as an endocrine disruptor, has emerged as an important risk factor for human breast cancer. The chemokine ligand 5 (CCL5) and its receptor CCR5 constitute a biological axis, that is implicated in tumorigenesis and cancer progression. However, the role of the CCL5/CCR5 axis in breast cancer when exposure to endosulfan remains unclear. The present study aimed to determine the significance of the CCL5/CCR5 axis in the carcinogenic effects of endosulfan in human breast cancer MCF-7 cells. The results showed that endosulfan significantly promoted cell proliferation, increased the rate of colony formation, and enhanced cell migration ability in a dose-dependent manner by activating the PI3K/AKT signaling pathway, which were rescued by the specific inhibitor (LY-294002) for PI3K/AKT signaling pathway. We utilized Cytoscape software to construct protein-protein interaction (PPI) network when exposure to endosulfan, and identified 47 highly connected genes in the network diagram centered on CCL5. Endosulfan significantly increased the secretion of CCL5 and the expression levels of CCL5/CCR5, which were reversed by CCR5 inhibitor (HY-13004). HY-13004 significantly counteracted the effects of endosulfan on colony formation, cell migration and the activation of PI3K/AKT signaling pathway. Endosulfan markedly altered the expression levels of epithelial-mesenchymal transition (EMT) biomarkers and enhanced transwell migration and invasion capabilities of MCF-7 cells, which were inhibited by HY-13004, similar to the effects observed with LY-294002. Collectively, our findings suggest that endosulfan activates the PI3K/AKT signaling pathway to promote cell growth, and induces EMT, thereby enhancing cell migration and invasion via the CCL5/CCR5 axis in MCF-7 cells.